SAMPLING AND REQUESTS AS BASIC GIS OPERATION OF DECISION GEOECOLOGICAL PROBLEMS - КОСТРІКОВ, С. В. (Man and Environment. Issues of Neoecology)
The paper represents the general concept of the GIS analytical capabilities provided through basic GIS-operations. Some particular procedures of these operations are described and discussed due to the geoecological subject area. Few examples of the regional environmental tasks are provided with their solutions through GIS-operations. It is proved that data selections and queries to both spatial and non-spatial information are the effective method, which can be performed for the areal environmental management. The paper provides some relevant interface examples from a well-known GIS-platform.